Antibacterial Activity Screening Of Bacterial Isolates Associated With Seaweed Eucheuma cottonii From Coastal Area In Buleleng, Bali - Purnami, Pande Putu Christine Putri; Indraningrat, Anak Agung Gede; Darmayasa, Ida Bagus Gede (Universitas Brawijaya, 2022)
Seaweeds like other marine organisms develop a strong association with prokaryotic communities, especially bacteria. Many of these associated bacteria play an important role in synthesizing secondary metabolites which are beneficial for their host, especially against predation or infection. In Indonesia, Eucheuma cottonii is one of the seaweed species that has been cultivated widely.Â However, only limited study has been reported on bacterial isolates and their antibacterial activity from E. cottonii.Â Bacterial isolates from E. cottonii were cultivated in six agar media namely Zobell Marine Agar, Nutrient Agar, Plate Count Agar, ISP-1, ISP-2, and Starch-M protein agar. Cultivation of bacterial isolates yielded 23 isolates with nine bacterial isolates were classified as Gram-positive bacteria and 14 isolates were grouped among Gram-negative bacteria. All the bacterial isolates were screened for their antibacterial activity against six bacterial indicator strains namely Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603 using perpendicular streak and agar block method. Six out of 23 bacterial isolates displayed antibacterial activity against at least one of the bacterial indicator strains. The bacterial isolate ISP1RL4 showed the highest antibacterial activity with average inhibition ofÂ > 20 mm against all bacterial indicators. Overall, our result indicated the potential of bacterial isolates associated with E. cottonii as an antibacterial producer.